Schizencephaly and Psychosis: A Rare Association - Matias Carvalho Aguiar Melo; Saulo Giovanni Castor Albuquerque; José Henrique Sousa Luz; Alexandre Bastos Lima (Case Reports in Medicine, 2013)
Schizencephaly is a rare malformation of the central nervous system defined as a gray matter-lined cleft filled with cerebrospinal fluid that extends from the pial surface to the ventricle. Few cases of association with psychosis were reported in the scientific literature. We present a case of a 46-year-old woman, admitted into a psychiatric hospital with crises of psychomotor agitation, disorganized and erotized behavior, persecutory and self-reference delusions, and auditory and visual hallucinations. She also reported seizures since her childhood. A head CT scan revealed a large subarachnoid space communication with the adjacent lateral ventricle in the topography of occipital, temporal, and parietal lobes to the right, suggestive of schizencephaly.